Endodontic Periodontic Lesions and Host Modulation - Case Series - Afaf Zia; Afshan Bey; Syed MUN. Andrabi; Saif Khan; Masood Khan (Faculty of Dentistry, Universitas Indonesia, 2015)
Host modulation, includes inhibition of matrix metalloproteinases, blocking production of proinflammatory cytokines and inhibition of osteoclastic activity, has therapeutic value as adjunctive therapy in treating chronic periodontitis. This case series presented three patients with chief complaint of teeth mobility where endo perio involvement was diagnosed. The endo perio combined lesions generally shows the communication between pulp and periodontal tissues with the same origin of dental infection. Diagnosis in such cases is difficult and generally raising problem in the management. All of the cases were managed by non surgical endodontic therapy combined with host modulation. All local factors causing the lesion were removed. Clinical outcome after six and nine months were quite satisfactory. Combined endo perio cases are challenging to the dentists and involve multidisciplinary involvement. To manage such cases, dentists have to rely on the unconventional techniques. DOI: 10.14693/jdi.v22i1.378